“At the Judge’s Discretion”: Challenges for Child Participation in Family Justice - Garcia-Quiroga, Manuela (2023)
In family justice, one of the biggest challenges is to effectively guarantee the right of children to participate. Though participation implies multiple benefits for the child, such as increased self-esteem, psychological wellbeing and preventing violations of rights, it is possible to detect many obstacles for it to effectively occur in court. Among these, prioritizing adults’ interests, conditioning participation of the child to their age and lack of formal regulations were noted. The present study consists of a thematic analysis of interviews with Chilean family judges about child participation. Findings point to a consideration of the infrastructure and the institutional legal organization as not being able to guarantee and facilitate child participation in the judicial system. Lack of standardization in norms and practices inside the courts encourages judges to base their decisions on their own personal abilities and criteria, frequently influenced by prejudice about revictimization and the capacity of children to exercise a meaningful participation related to their psychological development. In addition, considerations about how laws and family courts should promote child participation in family justice are discussed.